Jogos digitais e aprendizagens: o jogo Age of Empires III desenvolve idéias e raciocínios históricos de jovens jogadores? - Eucidio Pimenta Arruda (2009)
This research is situated in a field of work not only little explored but also permeated by some "pre" concept of the academy: the video games (computer games) and his relationship with the learning of history. My daily comments supported by some authors to suggest that young people with access to various digital media relations to create new knowledge, new ways of interpreting the world, and why not, new ways of learning and construction of historical knowledge. The aim of this study is to identify and analyze the learning of historical arguments and ideas that the players are subject through a computer game that simulates historical events. This survey had an essentially ethnographic nature, against my soaking for more than two years in the online environment of the game Age of Empires III, and had the sign paradigm for understanding the problem of research proposed. Among the main results of this work, highlight: Young people appreciate the interaction and the formation of social ties within and outside the game. The formation of clans, the organization around the game, the creation of forums for discussion and expansion of dialogue between them to aspects of daily life of each show that this couple does not want to be alone against the computer, but builds forms of socialization that in some moments, give the classic socializations presence. I was possible to observe that the young do not learn the history taught in school through the game, however, it operates with reasoning and ways of thinking historically that are fundamental to the understanding of history, to its position opposite the analytical past. Another aspect to be considered is the realization of their actions through the screen of the game - is a unique opportunity to visualize the implications of choices made by human data in context - in the case of the game, the choices made by the player. The atmosphere of the game makes this historical experience, it allows the couple view themselves as subject of history, as a character who changes the world by their actions. He also learns to tell stories, to understand the narrative dimension of their action in the game. There is a direct understanding - it does not expose this understanding through words or actions - the narrative was perceived between the lines of my comments. In general, it seems that there are learning and reasoning of these historical ideas in the actions of the players interviewed and observed, however, believe that the great contribution of this work is to build bridges and relationships between these strategies for learning in history and strategies for teaching and learning in history, used by teachers in the school environment. This work leaves open for teachers to create the bridges, the links between the history that is taught in school and ways of rationing that historically we learn through games, as well as launching other issues for future research.